The Effect Of Education And Training, Motivation And Discipline On Job Satisfaction As Intervening Variables On The Performance Of PNS Teachers In Public Elementary Schools In Panji District, Situbondo Regency - Yuli Anitasari, Eka; Yahya Arief, Mohammad; Ariyantiningsih, Febri (International Journal of Economics, Business and Innovation Research, 2025)
Education and training is important things​ for employee in something agencies. Employees who participate in education and training influence on the performance of civil servants. The more employee the active in work and follow in accordance rules and procedures, then the more good Civil Servant Performance obtained. Research​​ This aim For know The Influence of Education and Training, Motivation and Discipline with Satisfaction Work As Intervening Variables on the Performance of Civil Servant Teachers at Public Elementary Schools in Panji District, Panji Regency Situbondo. Based on framework the resulting conceptual, can concluded that Education and Training, Discipline influential positive significant to Satisfaction Work. Motivation influential positive However No significant to Satisfaction Work, and Education and Training, Discipline influential positive However No significant on Performance. Motivation and Satisfaction Work influential positive significant on Performance. Education and Training, Motivation and Discipline influential positive However No significant on Performance through Satisfaction Work.